State-religion relations in Southern and Southeastern Europe: moderate secularism with majoritarian undertones. Issue 4 (8th August 2022) - Magazzini, Tina; Triandafyllidou, Anna; Yakova, Liliya
ABSTRACT: This contribution studies comparatively three Southern European countries (Italy, Spain, and Greece) and three Southeastern European countries (Albania, Bosnia and Herzegovina, and Bulgaria). Looking beyond historical path-dependencies, we investigate recent developments in terms of state-religion relations. Starting with a thick description of the historical legacies and post-1989 developments, we focus on issues of the last decade, such as the rise of populism and nationalism, the path to EU accession for Bosnia and Albania, the economic and Eurozone crisis of the 2010s, and the refugee emergency of 2015. Our aim is to assess how these have shaped state-religion relations and to categorise the six countries within the typology proposed in the introductory contribution to this collection. Our findings suggest that moderate secularism and liberal neutralism prevail in all six countries. There are, however, important variations in terms of the relevance of majoritarian nationalism in some of them, as the state defines the prevailing religion and has strong historical and institutional ties with that religion. The contribution elaborates on these specificities and concludes with some questions on the importance of the notion of dominant vs qualifying norms and on the role of current challenges in shaping further state-religion relations.